Determinants of low fifth minute Apgar score among newborns delivered by cesarean section at Wolaita Sodo University Comprehensive Specialized Hospital, Southern Ethiopia: an unmatched case control study - Bahiru Darma Ajibo; Eskinder Wolka; Andualem Aseffa; Mitiku Ayele Nugusu; Abdi Oumer Adem; Mebratu Mamo; Ashagrie sintayehu Temesgen; Getachew Debalke; Negeso Gobena; Mohammad Suleiman Obsa (BMC, 2022)
Abstract Background Apgar score is used to evaluate the neonates' overall status and response to resuscitation, as well as its prognosis beyond the neonatal period. Low fifth minute Apgar scores is more frequent and is associated with markedly increased risks of neonatal mortality and morbidity. In Ethiopia, the prevalence of birth asphyxia is high (22.52%). Birth asphyxia contributes to significant neonatal morbidities and mortalities due to severe hypoxic-ischemic multi-organ damage, mainly brain damage. Therefore, this study was aimed to identify determinants of low fifth minute Apgar score among newborns delivered by cesarean section. Methods An unmatched case control study design was conducted. The Apgar score is based on measures of heart rate, respiratory effort, skin color, muscle tone, and reflex irritability. The data collection tool or checklist was adapted from previous study done at Addis Ababa, Ethiopia. In this study, cases were all newborns with Apgar score < 7 whereas controls were all newborns with Apgar score >  = 7. The study participants were selected by simple random sampling technique. Data was into Epidata version 4.6 and exported to SPSS software version 24. Multivariable logistic regression was used to identify the independent effect of different factors at P < 0.05. Result Factors associated with low Apgar score were fetal birth weight < 2.5 kg [adjusted odds ratio (AOR) = 8.17, 95% confidence interval (CI): 1.03 ‒ 64.59] P = 0.046, skin incision to delivery time (AOR = 5.27; 95% CI: 2.20 ‒ 12.60) P = 0.001, pregnancy induced hypertension (AOR = 4.58, 95% CI: 1.75 ‒ 11.92) P = 0.002, antepartum hemorrhage (AOR = 3.96; 95% CI: 1.75 ‒ 8.94) 0.001, general anesthesia (AOR = 3.37, 95% CI: 1.72 ‒ 6.62) P = 0.001, meconium stained amniotic fluid (AOR = 3.07, 95% CI: 1.32 ‒ 7.12) P = 0.009 and emergency cesarean section (AOR = 2.17, 95% CI: 1.13 ‒ 4.15) P = 0.019. Conclusions Fetal birth weight < 2.5 kg, skin incision to delivery time, pregnancy induced hypertension, antepartum hemorrhage, type of anesthesia, meconium stained amniotic fluid and type of cesarean section were factors independently associated with Apgar score. Therefore, it is important to work on identified risk factors to reduce the impacts low fifth minute Apgar score in the in early adulthood..